(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is dedicated to the study of the advantages of teaching psychological sciences to students of higher education institutions based on the module system. The article examines the quality of the intellectual potential of the information society, and such processes as a scientific and technical basis for the regular development of the information industry.